Analysis of Light Intensity from Various Types of Light Bulbs, Distance, and Time on Fruit Plants Dragon Fruit (Hylocereus Polyrhizus) in the Generative Phase - Syafrizal Hasibuan (Jurnal Penelitian Pendidikan IPA, 2025)
The study entitled analysis of light intensity from various types of distance and time bulbs with the aim of getting the appropriate type of light bulb, distance and time to increase dragon fruit production. The study was conducted in Kampung Melayu Village, Ujung Padang District, Simalungun Regency, North Sumatra Province with an altitude of ± 25 m above sea level. in April to June 2025. The study used Factorial RAK with 3 factors and 2 replications. The first factor of the type of light bulb consists of B1 = special light bulb for dragon fruit plants, B2 = LED light bulb, B3 = Special light bulb for chicken farms B4 = Incandescent light bulb. The second factor of the irradiation distance consists of J1 = 50 cm, J2 = 100 cm, J3 = 150 cm. The third factor of irradiation time W1 = 10 days of irradiation time W2 = 20 days of irradiation time W3 = 30 days of irradiation time The results of the study showed that treatment B1J2W2. Shows the highest dragon fruit production. This is because the light produced is like sunlight, the distance of the light from the plant is not close and not far from the distance of the dragon fruit plant and the lighting time is appropriate throughout the year because the light requirements for each month are different depending on the season.